3D Si/C Fiber Paper Electrodes Fabricated Using a Combined Electrospray/Electrospinning Technique for Li‐Ion Batteries. Issue 1 (18th August 2014) - Xu, Yunhua; Zhu, Yujie; Han, Fudong; Luo, Chao; Wang, Chunsheng
<x xml:space="preserve">Abstract</x> Although the theoretical capacity of silicon is ten times higher than that of graphite, the overall electrode capacity of Si anodes is still low due to the low Si loading and heavy metal current collector. Here, a novel flexible 3D Si/C fiber paper electrode synthesized by simultaneously electrospraying nano‐Si‐PAN (polyacrylonitrile) clusters and electrospinning PAN fibers followed by carbonization is reported. The combined technology allows uniform incorporation of Si nanoparticles into a carbon textile matrix to form a nano‐Si/carbon composite fiber paper. The flexible 3D Si/C fiber paper electrode demonstrate a very high overall capacity of ≈1600 mAh g‐1 with capacity loss less than 0.079% per cycle for 600 cycles and excellent rate capability. The exceptional performance is attributed to the unique architecture of the flexible 3D Si/C fiber paper, i.e., the resilient and conductive carbon fiber network matrix, carbon‐coated Si nanoparticle clusters, strong adhesion between carbon fibers and Si nanoparticle clusters, and uniform distribution of Si/C clusters in the carbon fiber frame. The scalable and facile synthesis method, good mechanical properties, and excellent electrochemical performance at a high Si loading make the flexible 3D Si/C fiber paper batteries extremely attractive for plug‐in electric vehicles, flexible electronics, space exploration, and military applications.